Quality assessment of three different treatments of minimally processed lettuce (Lactica Sativa Linn.) - Bolisay, Mildred San Pablo; Quijano, Ana Marie M. (2000)
ABSTRACT A quality assessment of the two minimally processed sample done by blanching and chlorination was analyzed in this study. The procedures were based from literature and previous studies on asepsis. Analysis of the sensory, microbial and physico-chemical qualities of untreated, blanched and chlorinated samples were done, and were compared to available standards set. An assessment of the minimal processing techniques based on the results of the tests was also done. Results of the sensory evaluation showed that the chlorinated sample held its quality for the longer period of time. It had the highest mean scores for both texture and color over six days of storage. The untreated samples followed next while the blanched sample had the lowest mean scores in terms of over-all acceptability. The physico-chemical tests showed that the pH and titrable acidity may be indicators of the microbiological make-up of the sample. All of the samples were neutral in pH range of 5.4-6.6 which lies in the danger zone in terms of microbial contamination (Jay, 1998). The three samples were within the limit of microbial standards in terms of all tests done, except for the coliform count. The untreated sample exceeded the coliform count from the first day of processing until the sixth day of storage. The blanched and chlorinated samples exceeded the limit of 2.0x10 raise to 2 during the third and sixth day of storage. The blanching treatment of the samples, when done adequately and to a point where the integrity of the samples may be preserved, may be the most effective minimal processing technique.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Vegetables -- Processing; Lettuce